Plant sucrose-H+ symporters mediate the transport of vitamin H. - Ludwig, Andreas; Stolz, Jürgen; Sauer, Norbert (Plant Journal, 2000)
A cDNA coding for a vitamin H (biotin) transport protein from Arabidopsis was identified by genetic complementation of a biotin uptake-deficient yeast mutant. Vitamin H transport by this protein was sensitive to the SH-group inhibitor p-chloromercuribenzene sulfonic acid (PCMBS) and to the uncoupler carbonyl cyanide-m-chlorophenylhydrazone (CCCP), suggesting an energy-dependent biotin-H+ symport mechanism. The transport activity could contribute to the so-far uncharacterized plant sucrose-H+ symporter AtSUC5 which mediates the energy-dependent transport of biotin and sucrose, and restores growth of the biotin transport-deficient yeast mutant on medium with low biotin concentrations. Functional comparison of the AtSUC5 transporter with previously characterized plant sucrose or monosaccharide transporters revealed that biotin transport may be a general and specific property of all plant sucrose transporters (sucrose/biotin-H+ symporters). This first report on a transporter with dual substrate specificity for two structurally unrelated molecules has a major impact on general thinking concerning the specificity of membrane transporters. The physiological relevance of this finding is discussed.